Changing strategy by the AKP: the power of populism in the 21st century - Mohamad Shukri, Syaza Farhana (2017)
Since 2014, Turkey has been moving towards a heightened sense of nationalism and populism with the election of Recep Tayyip Erdogan as the 12th president of Turkey. His anti-European Union (EU) rhetoric went up compared to when he became prime minister over a decade ago when the country was looking forward to forging a close relationship with the EU. Rather than putting a damper on the party, government, or Erdogan himself, his anti-EU rhetoric has helped consolidate his power, showcasing the amazing power of populism and nationalism during uncertain times. This paper borrows from behavioural psychology the concept of the learning curve theory or the S-curve theory. It is argued that after reaching a political peak with the Gezi Park protest in the summer of 2013, Erdogan is employing a different rhetorical approach—a populist one—to gain more political traction.